(untitled) (International Journal of Engineering and Computer Science, 2014)
Videoconferencing today is faced with the challenge of limited number of participants per time, and also the need for large and fully equipped conference rooms. This might not be a problem to a large enterprise, but for the small to medium-sized business, access to a videoconferencing facility involves either a very costly rental fee or is completely impossible. The aim of this work is to design and implement a videoconferencing prototype (OpenMeeting) with added functionalities which will solve problems facing the traditional way of conducting meetings.